2008
DOI: 10.1007/s11064-007-9547-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ischemic Effect of Curcumin in Rat Brain

Abstract: Turmeric has been in use since ancient times as a condiment and due to its medicinal properties. Curcumin, the yellow colouring principle in turmeric, is polyphenolic and major active constituent. Besides anti-inflammatory, thrombolytic and anticarcinogenic activities, curcumin also possesses strong antioxidant property. In view of the novel combination of properties, neuroprotective efficacy of curcumin was studied in rat middle cerebral artery occlusion (MCAO) model. Rats were subjected to 2 h of focal ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(67 citation statements)
references
References 43 publications
4
62
0
1
Order By: Relevance
“…Curcumin (Cur) is a phenolic compound that possesses multiple pharmacological properties including anti-oxidant, anti-inflammatory, anti-carcinogenic, antiischemic, hypotensive, and hepato-protective activities (Ammon and Wahl, 1991;Maheshwari et al, 2006;Shukla et al, 2008;Strimpakos and Sharma, 2008;Aggarwal and Sung, 2009). In the present study, co-exposure of Cur with NaAsO 2 mitigated the effects of the metal agent on cell viability, ROS generation, loss of MTP, and hypodiploid DNA content in murine splenocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin (Cur) is a phenolic compound that possesses multiple pharmacological properties including anti-oxidant, anti-inflammatory, anti-carcinogenic, antiischemic, hypotensive, and hepato-protective activities (Ammon and Wahl, 1991;Maheshwari et al, 2006;Shukla et al, 2008;Strimpakos and Sharma, 2008;Aggarwal and Sung, 2009). In the present study, co-exposure of Cur with NaAsO 2 mitigated the effects of the metal agent on cell viability, ROS generation, loss of MTP, and hypodiploid DNA content in murine splenocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin exerts neuroprotective functions such as anti-oxidation, anti-inflammation, anti-cancer, antiapoptosis, and immunomodulatory in animal models of ischemia, hemorrhage, and traumatic brain injury as well as SCI through crosstalk with multiple genes and cell-signaling pathways at multiple levels. [10][11][12][13] In spite of the above facts, little is known about the antiinflammatory mechanism of curcumin in spinal cord tissues after SCI. It has been demonstrated that curcumin inhibited the expression of NF-κB and the release of inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Products of these genes include SOD1 (cytosolic), SOD2 (mitochondrial), and SOD3 (extracellular) [86,87] and the peroxide detoxifying enzymes glutathione peroxidase [88] and catalase [89,90]. Nrf2 also mediates induction of glutamate-cysteine ligase catalytic subunit (GCLC) and glutamate-cysteine ligase, modifier subunit (GCLM), both of which are necessary for glutathione biosynthesis [91].…”
Section: Nrf2-regulated Antioxidant Defense Systemsmentioning
confidence: 99%